Nanostructured Materials and Catalytic Reactivity: A Theoretical Examination of Surface Chemistry Mechanisms - Maryam Maryam (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Nanostructured materials have transformed heterogeneous catalysis by introducing electronically and structurally heterogeneous surfaces whose reactivity cannot be explained through classical bulk descriptors. This study presents a non-empirical theoretical examination of surface chemistry mechanisms, constructing an integrative framework that correlates lattice distortion, facet-dependent coordination environments, vacancy formation energetics, and interfacial charge polarization with catalytic reaction pathways. Descriptor-based abstraction is employed to formalize structural perturbations into analytically tractable variables, enabling systematic interpretation of adsorption–activation–desorption sequences across material classes. The analysis demonstrates that catalytic performance arises from electronically mediated coupling between structural asymmetry and reaction coordinate modulation, while mechanistic competition is governed by interfacial charge dynamics and cross-site electronic communication. Stability–reactivity trade-offs are incorporated through thermodynamic constraint modeling, revealing that structural resilience and electronic activation are intrinsically interconnected. By synthesizing defect chemistry, surface thermodynamics, and electronic structure principles into a coherent explanatory scaffold, this work advances a predictive conceptual foundation for rational catalyst design. The framework offers transferable insight applicable to single-atom systems, core–shell architectures, and defect-engineered nanocomposites within sustainable catalytic technologies